Treating diabetic macular edema: comparative efficacy of 577 nm laser navigation exposure and threshold 532 nm laser coagulation combined with anti-angiogenic therapy - I. A. Krylova; N. V. Yablokova; O. L. Fabrikantov (Российский офтальмологический журнал)
The Navilas 577 laser system integrates a laser coagulator with a tracking system and a fundus camera. The system ensures operation planning and representing the results of optical coherence tomography on the fundus image, which makes the treatment fast, clearly observable and safe and minimizes damage to healthy tissues.Purpose. To compare the results of threshold laser coagulation in the treatment of DME using a Navilas 577 laser and a Quantel Medical 532 nm device.Materials and methods. 64 patients aged 41–80 (64 eyes) with DME less than 350 μm high were examined after intravitreal administration of angiogenesis inhibitors and threshold lattice laser coagulation using Quantel Medical 532 and Navilas 577.Results. A lower height of the edema and an increase in visual acuity were observed in both cases, but in the Navilas 577 laser group the BCVA was higher than in Quantel Madical 532, whilst the edema height in the Navilas 577 laser group in the central fovea area was less high.Conclusion. 1. The combination of retinal laser coagulation and angiogenesis inhibitors in the treatment of low DME (less than 350 μm) provides good results, so it can be justified and expedient in real clinical practice. The efficiency of 577 nm navigation laser exposure was found to be higher than that of threshold 532 nm laser coagulation.